Pendampingan Legalitas Usaha Kedai Panji Laras melalui Online Single Submission (OSS) Kelurahan Gedog Kecamatan Sananwetan - Firdha Amalia Nareswari; Wahyu Fahrul Ridho (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Business legality plays a very important role in Micro, Small and Medium Enterprises. Business legality is a business identity and a form of protection offered by the government to MSME actors. The problem that often occurs is that many UMKM do not understand how important business legality is. In addition, it is suspected that the complicated management of business legality is one of the causes of UMKM reluctance to take care of their legality. Therefore, the researchers assisted one of the UMKM in Gedog Village, namely Kedai Panji Laras, to legalize their business through Online Single Submissions (OSS). The purpose of this activity is to increase knowledge to business owners and also the community about the importance of NIB for micro and small businesses and to obtain an NIB certificate. The learning method used with preparation, manufacture and submission. The results of this activity are increasing the knowledge of business owners about the introduction of OSS and NIB, the importance of businesses having an NIB, the benefits of NIB, the requirements and procedures for making an NIB and the steps for making an NIB through OSS. The main objective of this activity is to issue NIB certificates for micro and small home-based chili sauce shops, Panji Laras